CHEMICAL INVESTIGATION OF MEDICAL MUD FROM LAKE NOGOON - G, Dolmaa; B, Bayaraa; B, Tserenkhand; B, Nomintsetseg; G, Ganzaya (Proceedings of the Mongolian Academy of Sciences, 2018)
The purpose of study was to determine chemical composition and organic matter of peloid from Nogoon Lake in Govi-Altai province by chemical and several analytical techniques. Based on these studies, it was identified that peloid belongs to silt sulphide muddy type, which is included the polymineral group. The content of macro and microelements in peloid from Nogoon was 0.0003-42.65%. Free organic matters in peloid were extracted using non-polar and polar solvents. Yield of total extract in peloid from Lake Nogoon was 1.479%. We determined chloroform-dissoluble organic matter (DOM) in total extract’s dry residue after consistently extracted by organic solvents. There were used chromato-mass-spectrometric method and identified 83 organic compounds in peloid from Lake Nogoon, that were containing hydrocarbons derivatives 33.68%, carboxylic acid 12.95%, dialkylphatalate (DAF) 3.09%, ketone 1.01% and nitrogen-containing compound 3.96%. The IR spectrum of peloid from Lake Nogoon showed СН2, СН3 alkanes group, carboxylic acid, ether (C-O) group, alkanes (CH) group absorption that free organic matter in peloid consist multiple compounds. We have developed a route for isolating and determining the composition of the organic compounds in peloids. Lipid group contain fat-soluble vitamins include vitamins A, D, E and their derivatives, steroids and other biological activity compounds which are similar to lipid by chemical and physical characterization. These compounds have shown lot of action such as oxidation and inflammation, microbial and membrane stabilization. Furthermore, the lipid fraction of the medical mud is widely used in cosmetics [1]. In the peloid from Lake Nogoon lipid matter contained 55 organic compounds alkanes 47.73%, DAF 5.58%, carboxylic acid 0.7%, ester 0.3 %, steroids 17.24%, oxygen organic compound 0.6%, and element sulfur 2.88%, nitrogen-containing compound 2.33%, silicon-containing compound 3.74%, cyclic hydrocarbons 0.27% respectively.